Religious Beliefs of World Boxing Champions as a Factor of Influence on Ukrainian Society in the Context of Social Responsibility - Synchak, Bogdan (Occasional papers on religion in Eastern Europe, 2022)
The issue regarding the influence of mass media on the public consciousness is one of the priorities in the times of the digitalization of the information space. Great sports such as professional boxing are world-famous and have a wide resonance in the media. As a result, scientists are paying attention to the study of factors of influence that arise during the information coverage of sporting events. Religious beliefs are a conditional plane of differentiation of different worldview systems, but in the 21st century, they are harmoniously integrated into the colors of different cultures, nationalities, and states. Celebrities’ religious beliefs can be influential factors that have certain results and consequences for society. This article considers the issue of social responsibility of world boxing champions for the public demonstration of their own religious beliefs as the example of the Ukrainian experience. The latter is relevant for the international community in the context of the rapid movement of Ukraine towards European integration and accession to NATO. The stated issues are considered in the example of media activity of Ukrainian world boxing champions, O. Usyk and V. Lomachenko. The problem is exacerbated against the background of the current Russian-Ukrainian hybrid war, where the plane of the religious worldview is actively used as a destructive factor of informational influence. In this context, this paper presents the data of the study of the coefficient of possibilities of informational influence of the Russian Federation on neighboring countries. The most resonant examples of media activity of Ukrainian world boxing champions on the topic of covering their own religious beliefs are demonstrated. Indicators of media potential of the influence of athletes' religious worldviews on society are analyzed.